On the crystallization of graphite from liquid iron–carbon–silicon melts. (1st April 2016) - Stefanescu, D.M.; Alonso, G.; Larrañaga, P.; De la Fuente, E.; Suarez, R.
Abstract: Extensive SEM work was carried out on deep etched specimens to reveal the evolution of graphite shape in Fe–C–Si alloys of industrial composition during early solidification and at room temperature. The samples had various magnesium and titanium levels designed to produce graphite morphologies ranging from coarse lamellar to interdendritic lamellar to mixed compacted – spheroidal. The present findings were then integrated in previous knowledge to produce an understanding of the crystallization of lamellar, compacted and spheroidal graphite. It was demonstrated that most forms of graphite grow radially from a common center, most of the time as foliated dendrites (see Figure). The basic building blocks of the graphite aggregates are hexagonal faceted graphite platelets with nanometer height and micrometer width. During solidification, thickening of the platelets occurs through growth of additional graphene layers nucleated at the ledges of the graphite prism. In the magnesium-free irons that graphite platelets assemble into foliated crystals and dendrites, forming graphite plates that grow along the a -axis. In the magnesium-modified melts the graphite platelets stack along the c -axis, producing clusters with random orientation. The clusters are then assembled into quasi-cylindrical shapes connected to more or less curved walls to form tadpole graphite, compacted graphite, or chunky graphite. If enough magnesium is added, conical sectors made of platelets stacked in the c -direction grow from the same nucleus. The conical sectors may occupy the whole volume of the sphere forming a graphite spheroid, or only part of it like in chunky graphite. The large number of cavities observed between the platelets is consistent with growth of foliated dendrites. Graphical abstract: